2010
DOI: 10.1007/s11249-010-9729-7
|View full text |Cite
|
Sign up to set email alerts
|

Film Thickness of Ionic Liquids Under High Contact Pressures as a Function of Alkyl Chain Length

Abstract: Ionic liquids are generally considered as environmentally friendly material. The film thicknesses of ionic liquids and silicone oils at high pressures up to 3 GPa are measured employing the relative optical interference intensity method. The results show that for the three ionic liquids the relative order of film thickness is 1-octyl-3-methylimidazolium hexafluorophosphate ([OMIM]PF 6 ) [ 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM] PF 6 ) [ 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 30 publications
0
35
0
2
Order By: Relevance
“…At a pressure of 1 GPa, they found that the central film thickness increased from 10 nm for butyl-methylimidazolium PF 6 to 22 nm for octyl-methylimidazolium PF 6 . They suggested that the increased alkyl chain length was likely to result in a more orderly, denser and thicker layer [63]. In the field of tribology, the theoretical film thickness of traditional lubricants under pressure are calculated using equations, such as those developed by Dowson and Hamrock [64].…”
Section: Fundamental Studies Of Confined Ilmentioning
confidence: 99%
“…At a pressure of 1 GPa, they found that the central film thickness increased from 10 nm for butyl-methylimidazolium PF 6 to 22 nm for octyl-methylimidazolium PF 6 . They suggested that the increased alkyl chain length was likely to result in a more orderly, denser and thicker layer [63]. In the field of tribology, the theoretical film thickness of traditional lubricants under pressure are calculated using equations, such as those developed by Dowson and Hamrock [64].…”
Section: Fundamental Studies Of Confined Ilmentioning
confidence: 99%
“…Ionic liquids in high confinement were also investigated by Xiao et al [89], because of their unique properties. The longer length of the alkyl side chain of the ionic liquid results in lubrication films that are thicker than those of silicone oils with similar viscosity, as shown in Fig.…”
Section: Tfl At High Applied Loadmentioning
confidence: 99%
“…During the last decade, imidazolium-base ionic liquids with fluorinated anions have been specially addressed in a number of studies [1,[15][16][17]. The application range of the imidazolium ILs was further expanded by rational designing of the molecular structure and the side chains offering the possibility of obtaining versatile ILs with tailored polarity, hydrophobicity, and corrosive and antioxidant properties [7,[18][19][20][21][22][23][24][25]. Generally, the increase of the length of the alkyl side chains attached to a cation head group leads to the improvement of wear resistance, but this effect is not straightforward [2,22,26].…”
Section: Introductionmentioning
confidence: 99%
“…The application range of the imidazolium ILs was further expanded by rational designing of the molecular structure and the side chains offering the possibility of obtaining versatile ILs with tailored polarity, hydrophobicity, and corrosive and antioxidant properties [7,[18][19][20][21][22][23][24][25]. Generally, the increase of the length of the alkyl side chains attached to a cation head group leads to the improvement of wear resistance, but this effect is not straightforward [2,22,26]. Substitution of alkyl chains by poly(ethylene glycol) (PEG) improved the tribological performance of the IL, although at the cost of decreasing its thermal stability [8,27].…”
Section: Introductionmentioning
confidence: 99%